Hydroxyapatite particles substituted with Pd ions for remarkable antibacterial performance - Jeong, Seung-Jae; Jeong, Yoon-Seop; Jeong, Jae-Won; Lee, Heesoo; Kwon, Young-Tae (Frontiers in Chemistry, 2025)
The increasing threat of bacterial infections to human health has positioned the development of antibacterial materials as a critical global research priority. Recently, hydroxyapatite (HAP), which is chemically similar to the main components of bone and teeth, has attracted considerable attention as a promising antibacterial material due to its ability to inhibit bacterial adhesion and proliferation through electrostatic repulsion. However, hydroxyapatite exhibits lower antibacterial activity compared to metal particles or metal ions, which remains a limitation for its application as an antibacterial agent. Here, we present simple and one-step synthesis of the hydroxyapatite particles partially substituted with palladium (Pd) ions. The designed reaction simultaneously allows the formation of HAP particles and the substitution of Calcium ions (Ca2+) with Pd2+ ions within the HAP lattice. While the pure HAP particles show an antibacterial activity of approximately 97.5%, Pd-5% substituted HAP demonstrates ultrahigh antibacterial performance exceeding 99.9% against three different bacteria, including Staphylococcus aureus, Klebsiella pneumoniae, and Escherichia coli. This study comprehensively investigates the correlation between the Pd substitution and antibacterial ability, providing valuable insights for the development of advanced antibacterial materials aimed at promoting human health and a safe, clean environment.